Repair or Reconstruction in Acute Posterolateral Instability of the Knee: Decision Making and Surgical Technique Introduction - Stannard, James P.; Stannard, James T.; Cook, James L. (The Journal of Knee Surgery, 2015)
Complex knee injury surgeons must frequently decide whether to repair or reconstruct an acute posterolateral corner (PLC) injury. If repair is not feasible or fails, reconstruction is often necessary. Several studies have found that reconstruction has better outcomes and lower failure rates. Careful studies of the anatomy of the corner have led to the development of “two-tailed” reconstruction techniques which are becoming widely used in the field. Repair should not be completely disregarded as there are times when it is necessary, especially when no donor allograft tissue is readily available or when aggressive postoperative rehabilitation will not be performed. Optimally, if the patient has high quality tissue available for repair, it is best to combine reconstruction with repair. The authors have developed a new PLC reconstruction technique which applies the functional anatomy that has been increasingly defined. We detail these methods here, which include the use of cortical button suspensory fixation and interference screw fixation of allografts in sockets. This allows for individual and sequential intraoperative tensioning of the grafts to obtain optimal knee stability and motion.
Keywords: posterolateral corner; repair; reconstruct; popliteus